Effects of air pollution on daily hospital admissions for respiratory disease in London between 1987-88 and 1991-92. (April 1996) - Ponce de Leon, A; Anderson, H R; Bland, J M; Strachan, D P; Bower, J
Abstract : STUDY OBJECTIVE: To investigate whether air pollution levels in London have short term effects on hospital admissions for respiratory disease. DESIGN: Poisson regression analysis of daily counts of hospital admissions, adjusting for effects of trend, seasonal and other cyclical factors, day of the week, holidays, influenza epidemic, temperature, humidity, and autocorrelation. Pollution variables were particulates (black smoke: BS), sulphur dioxide (SO2), ozone (O3), and nitrogen dioxide (NO2), lagged 0-3 days. SETTING AND PATIENTS: All immediate admissions for respiratory disease (ICD 460-519) to hospitals in London health districts in the five years April 1987 to February 1992 for all ages and the 0-14, 15-64, and 65+ age groups. MAIN RESULTS: O3 (lagged one day) was significantly associated with an increase in daily admissions among all age groups, except the 0-14 group, and this effect was stronger in the "warm" season (April-September). In this season, the relative risks of admission associated with an increase in 8 hour O3 levels of 29 ppb (10th to 90th centile) were 1.0483 (95% CI 1.0246, 1.0726), 1.0294 (0.9930, 1.0672), 1.0751 (1.0354, 1.1163), and 1.0616 (1.0243, 1.1003) for all ages and age groups 0-14, 15-64, and 65+ respectively. Very few significant associations were observed with the other pollutants, though these tended to be positive. Controlling for other pollutants made little difference to the O3 coefficients. There was evidence of a threshold at about 40-60 ppb O3 (maximum hourly or maximum 8 hour). CONCLUSIONS: O3 levels in London have a small but significant effect on hospital admissions for respiratory disease at all ages. The possible role of aerollergen as a confounding factor needs to be examined. Unlike other cities where similar effects have been reported, little or no effect of particulates was observed in London.